2022
DOI: 10.1539/eohp.2022-0001-oa
|View full text |Cite
|
Sign up to set email alerts
|

Examining the associations of using the Calm app with team mindfulness and psychological safety in remote workers

Abstract: Objective:The purposes of this study were to (1) illustrate how remote workers engage with an employer-provided mindfulness meditation app in the workplace and (2) examine the relationship between workplace app engagement, team mindfulness, and psychological safety among remote workers. Methods: A cross-sectional survey was administered to employees within the United States who had received a subscription to Calm as part of their health benefits. Employees reported on three types of engagement with the Calm ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Considering the popularity of music in the Calm app and many consumer-based mobile apps that offer similar music content, future studies are warranted to determine the effects of music on mental health and productivity. Furthermore, as is to be expected, we observed variable engagement across work sites, which could indicate other site-level characteristics (eg, workplace culture, networks of communication, and psychological safety within a team) that may have differentially influenced uptake across sites [ 66 , 67 ]. Future pragmatic trials implementing the Calm app in the workplace setting would benefit from additional consideration of these key contextual drivers of reach and uptake.…”
Section: Discussionmentioning
confidence: 84%
“…Considering the popularity of music in the Calm app and many consumer-based mobile apps that offer similar music content, future studies are warranted to determine the effects of music on mental health and productivity. Furthermore, as is to be expected, we observed variable engagement across work sites, which could indicate other site-level characteristics (eg, workplace culture, networks of communication, and psychological safety within a team) that may have differentially influenced uptake across sites [ 66 , 67 ]. Future pragmatic trials implementing the Calm app in the workplace setting would benefit from additional consideration of these key contextual drivers of reach and uptake.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, some studies used commercially available apps (and, thus, ones not tailored to companies) to test their effectiveness among their target group. Examples of these apps are the Calm app [ 43 , 57 ] and Headspace. Effectiveness in terms of, e.g., stress perception, perceived mindfulness and perceived well-being could be demonstrated [ 27 , 34 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…One such study, by Hwang et al (2019), found significant changes in the experimental group in terms of stress, emotional labour, well-being and self-efficacy. Other studies focussed on public school staff [ 32 ], male-dominated industries [ 54 ], pharma employees [ 27 ], university staff [ 40 , 46 ], governmental organisational staff [ 25 , 42 ], remote workers [ 57 ], or entrepreneurs [ 53 ], or else included different employers [ 26 , 38 , 58 ]. The remaining 15 studies investigated office workers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations